The animator's survival kit - Williams, Richard, 1933-2019 (Faber and Faber, 2009)
The Academy Award-winning artist draws on his master instruction classes to demonstrate essential techniques required of animators of any skill level or method, in an updated edition that provides expanded coverage of such topics as animal gaits and live action
"A manual of methods, principles and formulas for classical, computer, games, stop motion and internet animators."--Obálka
Keywords: filmová animace; kreslířské techniky; film animation; drawing techniques; příručky; handbooks, manuals, etc